Ectopic Expression of O Antigen in Bordetella pertussis by a Novel Genomic Integration System - Keisuke Ishigaki (American Society for Microbiology, 2018)
ABSTRACT We describe a novel genome integration system that enables the introduction of DNA fragments as large as 50 kbp into the chromosomes of recipient bacteria. This system, named BPI, comprises a bacterial artificial chromosome vector and phage-derived gene integration machinery. We introduced the wbm locus of Bordetella bronchiseptica, which is required for O antigen biosynthesis, into the chromosome of B. pertussis, which intrinsically lacks O antigen, using the BPI system. After the introduction of the wbm locus, B. pertussis presented an additional substance in the lipooligosaccharide fraction that was specifically recognized by the anti-B. bronchiseptica antibody but not the anti-B. pertussis antibody, indicating that B. pertussis expressed O antigen corresponding to that of B. bronchiseptica. O antigen-expressing B. pertussis was less sensitive to the bactericidal effects of serum and polymyxin B than the isogenic parental strain. In addition, an in vivo competitive infection assay showed that O antigen-expressing B. pertussis dominantly colonized the mouse respiratory tract over the parental strain. These results indicate that the BPI system provides a means to alter the phenotypes of bacteria by introducing large exogenous DNA fragments. IMPORTANCE Some bacterial phenotypes emerge through the cooperative functions of a number of genes residing within a large genetic locus. To transfer the phenotype of one bacterium to another, a means to introduce the large genetic locus into the recipient bacterium is needed. Therefore, we developed a novel system by combining the advantages of a bacterial artificial chromosome vector and phage-derived gene integration machinery. In this study, we succeeded for the first time in introducing a gene locus involved in O antigen biosynthesis of Bordetella bronchiseptica into the chromosome of B. pertussis, which intrinsically lacks O antigen, and using this system we analyzed phenotypic alterations in the resultant mutant strain of B. pertussis. The present results demonstrate that this system successfully accomplished the above-described purpose. We consider this system to be applicable to a number of bacteria other than Bordetella.